2018
DOI: 10.1016/j.mseb.2017.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Novel magnetic nanocomposites containing quaternary ferrites systems Co0.5Zn0.25M0.25Fe2O4 (M = Ni, Cu, Mn, Mg) and TiO2-anatase phase as photocatalysts for wastewater remediation under solar light irradiation

Abstract: Cool Pegie, Seftel Elena.-Novel magnetic nanocomposites containing quaternary ferrites systems (M = Ni, Cu, Mn, Mg) and -anatase phase as photocatalysts for w astew ater remediation under solar light irradiation Materials science and engineering: part B: solid state materials for advanced technology -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The micrograph shows that two forms of nanoparticles are present. Dark contrast particles showed a spherical form with a random orientation and an average size of >50 nm, consisting in a CCMF ferrimagnetic phase in the structure [36]. For the CCMF sample a closer investigation into the HR-TEM image shows the presence of two types of crystallites that can be well correlated to the XRD observations.…”
Section: Tem and Edx Studymentioning
confidence: 58%
“…The micrograph shows that two forms of nanoparticles are present. Dark contrast particles showed a spherical form with a random orientation and an average size of >50 nm, consisting in a CCMF ferrimagnetic phase in the structure [36]. For the CCMF sample a closer investigation into the HR-TEM image shows the presence of two types of crystallites that can be well correlated to the XRD observations.…”
Section: Tem and Edx Studymentioning
confidence: 58%
“…Ciocarlan et al [117] evaluated the structural, morphological, and photocatalytic properties of magnetic nanoparticles Co 0.5 Zn 0.25 M 0.25 Fe 2 O 4 /TiO 2, where M represent Ni 2+ , Cu 2+ , and Mn 2+ ions. XRD patterns for TiO 2 -based magnetic nanocomposites showed that the introduction of TiO 2 into the magnetic nanoparticles affected their structural properties (Figure 12).…”
Section: Mixed-metal Ferrites and Nanocompositesmentioning
confidence: 99%
“…Finally, in terms of photocatalytic activity, the results demonstrated that approximately 80% and 75% of methylene orange (MO) and methylene blue (MB) were effectively degraded by Co0.5Zn0.25Ni0.25Fe2O4/TiO2. The authors attributed the good photocatalytic activity to the Ni 2+ ions and synergistic effect in combination with Co 2+ ions [117]. This section may be divided by subheadings.…”
Section: Mixed-metal Ferrites and Nanocompositesmentioning
confidence: 99%
“…The water pollution is a serious threat to human health and aquatic life all over the world (Fiorenza et al 2018). The large amount of water used in textile industry for various processes released to aquatic environment along with toxic organic dyes (Ciocarlan et al 2018). The products resulting from photochemical oxidation and hydrolysis reactions occurred in wastewater containing organic dyes are harmful to aquatic life.…”
Section: Introductionmentioning
confidence: 99%